PROSPECTS OF THE VETERINARY SECTOR ON THE PATH TO DEVELOPMENT OF UZBEKISTAN - Samiev Abdullo (Western European Studies, 2025)
This article analyzes the role and prospects of the veterinary sector in the development of Uzbekistan. The veterinary system plays an important role not only in the sustainable development of animal husbandry and agriculture, but also in human health, food safety and environmental protection. The article discusses the current state of the veterinary service in Uzbekistan, areas for its improvement, opportunities for the introduction of modern technologies and innovative approaches that meet international standards. It also highlights best practices in preventing animal diseases, strengthening the veterinary and sanitary control system, and improving legislation in the field.
Keywords: Veterinary medicine of Uzbekistan; the path of development; veterinary sector